An Opinion Survey on FTP System among Branch Managers of Commercial Banks of Nepal - Gautam, Chintamani (PYC Nepal Journal of Management, 2016)
Funds Transfer Pricing (FTP) is a process that assigns funding costs to asset originators (loans) and funding credits to liability providers (deposits). It is one of the powerful and useful components of any profitability measurement system for financial institutions. This study aimed to survey the opinions of branch managers of Nepalese Commercial Banks in order to measure the awareness about FTP and to collect opinions regarding its practice in Nepal. A total of 140 branch managers were approached for the data collection. Out of them only 88 branch managers were found having awareness on FTP system. Therefore, detail analysis was made on the basis of responses of only 88 respondents. The survey revealed that Nepalese branch managers agree on the advantages of FTP system in bank branches, but they lacked enough skill of FTP system. The awareness of branch managers is depended more on their work experience than on job level of managers.